Dry Swab-Based Nucleic Acid Extraction vs. Spin Column-Based Nucleic Acid Extraction for COVID-19 RT-PCR Testing: A Comparative Study - Mohammed Faraaz Khan; C. Roopa (Canadian Journal of Infectious Diseases and Medical Microbiology)
Conventional nucleic acid extraction involves usage of spin columns to isolate the RNA, but this is labor intensive. This study compares the spin column method with a dry swab-based method of extraction using a proteinase K buffer and subsequent heat inactivation. A total of 56 subjects were tested for COVID-19 by RT-PCR with probes targeting the E and RdRp genes by collecting two nasopharyngeal and two oropharyngeal swabs and subjecting one set to nucleic acid extraction by spin column and the other set to dry swab-based methods. Out of the 56 samples tested, 27 were positive for VTM-based extraction and 29 were negative. Dry swab-based extraction produced 22 positive results (sensitivity = 81.48%) and 34 negative results. The E gene was detectable in 25 samples by the dry swab method out of 27 samples that tested positive by the VTM-based method (sensitivity = 92.5%). The RdRp gene was detectable in 22 samples by the dry swab method out of 27 samples that tested positive by the VTM-based method (sensitivity = 81.48%). Concordance was 91% with discordance at 9% and a Kappa value of 0.82, indicating almost perfect agreement between the two methods. Our findings indicate that the dry swab method of nucleic acid extraction is a useful alternative to conventional spin column-based extraction with comparable sensitivity and specificity. The trial was registered with the Clinical Trials Registry of India (CTRI) with a CTRI registration number of CTRI/2021/12/038792.